2017
DOI: 10.1061/(asce)co.1943-7862.0001295
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Transition Pathways toward Sustainability for Construction Enterprises: Importance-Performance Analysis

Abstract: There has been growing awareness and demand for construction enterprises transition towards sustainability with an aim to maximize the economic, social and environmental values of construction. This presents a significant challenge to both policy makers and industry practitioners as sustainability is such a complex concept that includes various aspects whereas construction firms are usually resource constrained. There is lack of studies classifying various aspects of sustainability according to their manageria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 51 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…The results clarify that the variable 'professional fees of engineers and consultants' was ranked first with mean = 3.29 and RII = (65.81%). These results are consistent with those of the study [23] who reported that this variable is important because it has a managerial focus, that is, engineers and consultants control most other variables affecting sustainability performance during the construction stage of project development. The factor 'energy cost' came second with mean = 3.23 and RII = (64.52%).…”
Section: Economic Sustainability Factorsupporting
confidence: 92%
See 1 more Smart Citation
“…The results clarify that the variable 'professional fees of engineers and consultants' was ranked first with mean = 3.29 and RII = (65.81%). These results are consistent with those of the study [23] who reported that this variable is important because it has a managerial focus, that is, engineers and consultants control most other variables affecting sustainability performance during the construction stage of project development. The factor 'energy cost' came second with mean = 3.23 and RII = (64.52%).…”
Section: Economic Sustainability Factorsupporting
confidence: 92%
“…Waste management [10,23,45] Depletion of dependency resources (water-energy-raw materials-land) [6,10,15,23,25,29,43,44,46] Site attributes [38] Pollution generation [10,15,23,25,45] Natural habitat destruction [15,22] Changes in the environment lead to the discomfort of people and the biological system. [15,22] Health and safety risks [15,22] Where, SS = Sample Size; Z = Z value (e.g.…”
Section: Sample Sizementioning
confidence: 99%
“…Since then, Importance-Performance Analysis has been widely employed in management studies [21][22][23]. In the construction context, Importance-Performance Analysis has been conducted in order to understand the sustainability attitude and initiatives of construction enterprises and their employees [24][25][26]. The entire research process is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is a common approach to employ a quantitative approach in previous studies related to Importance-Performance Analysis. One of most common approaches is to employ a five-point Likert scale to measure importance and performance [25][26][27]. Therefore, a five-point Likert scale was employed in this study to measure the importance and performance levels of the management of each individual risk perceived by industry practitioners.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, IPA can analyze the results to improve the scheduling of the program and help the industry to improve its service, as well as customer satisfaction [42]. Chang et al (2017) [43] apply the importance-performance analysis (IPA) to analyze the transition pathways toward sustainability for construction enterprises. Liao and Lou (2013) [44] apply the analysis network process (ANP) and importance-performance analysis (IPA) to analyze the service quality and customer satisfaction of home-delivery service providers in the Taiwan market.…”
Section: Importance-performance Analysismentioning
confidence: 99%